On how to identify a seminal fluid protein: A commentary on Hurtado et al. Issue 5 (17th August 2022) - Wigby, Stuart; Brown, Nora C.; Sepil, Irem; Wolfner, Mariana F.
Abstract : Seminal fluid proteins (Sfps) have striking effects on the behaviour and physiology of females in many insects. Some Drosophila melanogaster Sfps are not highly or exclusively expressed in the accessory glands, but derive from, or are additionally expressed in other male reproductive tissues. The full suite of Sfps includes transferred proteins from all male reproductive tissues, regardless of expression level or presence of a signal peptide.